El matrimonio de parejas del mismo sexo y la Corte Constitucional de Colombia (2018)
In Colombia, gay people are part of a group that has been historically marginalized and discriminated, including by the law. The Constitutional Court has played a leading role in the recognition of rights to homosexuals; from an evolutionary interpretation, it has been extending its protection, first, the exercise of individual rights without discrimination and later to rights to form a family and marriage. Since June 30, 2013, the same-sex couples were empowered by a judgment of the Constitutional Court to appear before notaries and judges of the Republic to formalize and solemnize their union through a contractual link. The problem raised in this article is about the jurisdiction of the Court to intervene in matters that are the exclusive configuration of Congress. The authors do a documentary review of jurisprudence of the Court and of national and international laws to respond to this problem. © 2018 Universidad Austral de Chile.